THE RELATION BETWEEN THE NEUTROFIL LYMPHOCYTE RATIO (NLR) AND THE DEGREE OF DENGUE HEMORRHAGIC FEVER IN THE INPATIENT INSTALLATION OF ARI CANTI HOSPITAL FOR THE PERIOD OF APRIL 2022 – MAY 2023 - mahayanti, kadek seri; Suardamana, Ketut (E-Jurnal Medika Udayana; Vol 13 No 1 (2024): E-Jurnal Medika UdayanaDO - 10.24843/MU.2024.V13.i01.P02, 2024)
Dengue Hemorrhagic Fever is caused by dengue virus infection which can cause death and cause an outbreak. Neutrophil lymphocyte ratio (NLR) is one of the cheap laboratory parameters and can predict plasma leakage in the critical period of dengue hemorrhagic fever. This study aims to determine the profile of dengue hemorrhagic fever patients and the relationship between the neutrophil lymphocyte ratio and the degree of dengue hemorrhagic fever in patients treated at Ari Canti Hospital for the period April 2022 – May 2023.  This research is a retrospective analytical study with a cross-sectional approach using secondary data from archives at the Ari Canti Hospital Inpatient Installation for the period April 2022-May 2023. Data collection in the form of gender, age, neutrophil lymphocyte ratio and degree of dengue hemorrhagic fever was carried out using the convenient purposive sampling method. This study shows that the highest age group is the 26-35-year age group 35.7%, the highest gender is male 55.3% with cases of dengue hemorrhagic fever without shock 89.2% and a neutrophil lymphocyte ratio (NLR) of >2 as much as 64.2%. The result of  Mann Whitney non-parametric test, showed that p value <0.0001. There is a significant relationship between NLR and the degree of dengue hemorrhagic fever in patients hospitalized at Ari Canti Hospital in April 2022, May 2023. Keywords : dengue virus., dengue hemorrhagic fever., hospitalization., neutrophil lymphocyte ratio